Weak Anti-inflammatory and Anti-cancer Properties of Saffron - Mohammad Hossein Heidari; Zahra Razzaghi; Mohammad Rostami-Nejad; Sina Rezaei-Tavirani; Saeed Safari; Mostafa Rezaei-Tavirani* (Iranian Society of Pharmacognosy, 2020)
Background and objectives: Positive role of saffron in human health promotion has been investigated in widespread researches. Anticancer property, neuroprotection, protection of cardiovascular system and several positive properties are reported for saffron customers. The aim of this study was assessment of saffron weakness against light damage in rat retina. Methods: Gene profiles of control samples (C group) and light damage (L) groups were extracted from Gene Expression Omnibus (GEO) and compared with similar samples in the presence of saffron. The unprotected differentially expressed genes (DEGs) were evaluated via network analysis and pathway investigation.  The critical genes which were not protected by saffron were identified and discussed. Results: Numbers of 67 DEGs were investigated via protein-protein interaction (PPI) network analysis, pathway assessment, and action map investigation. Findings indicated that STAT1, JUN, FOS, and STAT3 were the crucial genes that were not protected by saffron against light damage in rat retina. Conclusion: It may be necessary that consumption of saffron require a suitable protocol to avoid from possible disadvantages; however, saffron is well known for its benefits in human nutrition.